(Dis-)engaged older men? Hegemonic masculinity, fashion and ageing. Issue 3 (1st December 2017) - Sadkowska, Ania; Townsend, Katherine; Fisher, Tom; Wilde, David
Recently, we have witnessed an intensified interest from various fashion scholars on the subject of men and masculine identities. However, while most of the existing research initiatives explore various aspects of masculinity and fashion, they also seem to be limited in their choices of subjects to homosexual and/or young male adults. In this vein, Julia Twigg argues that older men remain 'largely disengaged from fashion as a cultural field' (2013a: 19). This article explores the nature of this theoretical disengagement when it comes to older heterosexual men's lived experience of fashion by drawing on in-depth, semi-structured interviews and personal inventories with a small sample of British men (n=5) based in, or strongly linked to, Nottingham, United Kingdom. In-depth qualitative analysis of the research material revealed various contradictions displayed by the participants in relation to their ageing masculine identities and their often lifelong interest in fashionable clothing. We inspect these discrepancies from two perspectives in which such a disengagement might emerge: between men and fashion and between fashion and ageing. By analysing the findings through Connell's (2005) influential concept of hegemonic masculinity, we argue that some men both resist and reproduce such a stereotypical disengagement.